THE APPLICATION OF BRAIN-BASED LEARNING APPROACH IN TEACHING READING COMPREHENSION TO THE FIRST YEAR STUDENTS OF MA AS’ADIYAH ERENG-ERENG BANTAENG - Bustang, Bustang (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The objective of this research was to describe the application of Brain-Based Learning Approach to be used in teaching reading comprehension to the first year students of MA As?adiyah Ereng-Ereng Bantaeng Regency.The method used in this research was descriptive quantitative method that is one group, post-test classification. problems statement of this research is what is the students? reading comprehension after the application of Brain-Based Learning Approach to the first year students of MA As?adiyah Ereng-Ereng Bantaeng?. There were two variables, namely independent variable (the application of Brain Based Learning Approach) and dependent variable (Teaching Reading Comprehension).The population of this research was the first year students of MA As?adiyah Ereng-Ereng Bantaeng Regency in academic year 2019/2020.The total number of population was 22 students. The sample of the research was 22 students which were taken by using total sampling technique.The instrument of this research was reading comprehension test. The result of the data indicated that there was a good classification.  The mean score of the test section was 80  and standard deviation in post-test was 9.1.Based on the finding and discussion of the research, the researcher drawn a conclusion that the application of Brain Based Learning Approach was good to be used in teaching reading comprehension to first year students of MA As?adiyah Ereng-Ereng.